Tradisi Mangupa-Upa Dalam Adat Mandailing Menurut Hukum Islam: Studi Kasus Di Desa Tangga Bosi III, Siabu, Kabupaten Mandailing Natal-Sumatera Utara - Indra Wahyudi; Habibullah Ritonga; Sulaiman Tamba (Jurnal Ekshis, 2026)
This tradition functions not merely as a cultural ritual, but also embodies religious, social, and moral values deeply rooted in the daily life of the community. This study aims to examine the implementation of the Mangupa Upa tradition and to analyze its position from the perspective of Islamic law, particularly through the concept of ‘urf. This research employs a qualitative approach using field research methods. Data were collected through observation, in-depth interviews with traditional leaders, religious figures, and community members, as well as documentation related to the practice of Mangupa Upa. The data were analyzed using a descriptive-analytical method by linking empirical findings with Islamic legal principles and ‘urf theory. The findings indicate that the Mangupa Upa tradition in Tangga Bosi III Village remains well preserved and is regarded as a significant marker of Mandailing social identity. The tradition has undergone a process of value transformation, in which elements potentially conflicting with Islamic creed have gradually been abandoned and replaced by Islamic practices such as collective prayers, remembrance (dhikr), recitation of Surah Al-Fātiḥah, and expressions of gratitude to Allah SWT.